2021
DOI: 10.1109/access.2021.3090907
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Learning for Vehicle Lateral Stability Estimations

Abstract: Precise estimations of the roll and sideslip angles of autonomous vehicles are essential for autonomous driving, which requires further information about the vehicle state. As such, novel deep learning approaches have been introduced for this purpose. However, the majority of deep learning works focusing on vehicle dynamics estimations have yet to delve into learning strategies specifically for this task. Here, we argue that simply applying an adequate learning strategy to the task can boost the estimation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A lateral offset distance of more than 30 cm is usually suggestive of a vehicle sideslip. Roll angle, sideslip angle, side friction coefficient, and yaw angle are additional important indicators for assessing vehicle lateral stability [40][41][42][43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A lateral offset distance of more than 30 cm is usually suggestive of a vehicle sideslip. Roll angle, sideslip angle, side friction coefficient, and yaw angle are additional important indicators for assessing vehicle lateral stability [40][41][42][43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Mean Squared Error (MSE) loss was used as the loss function and the Adam optimization was used for mini-batch gradient descent. We collected a human-controlled driving dataset in a manner similar to that utilized in our prior work on the training of a dynamics model [23]. The vehicle state is defined as x = [v x , v y , r] T , where v x and v y are the longitudinal and lateral velocities, and r is the yaw rate.…”
Section: B Training the Neural Network Vehicle Modelmentioning
confidence: 99%
“…We also evaluated the performances of different controllers in a high-fidelity vehicle simulator, the IPG CarMaker. It has been widely used to validate precisely nonlinear vehicle dynamics [21]- [23]. We built a race track with a length of 1016 m, two moderate curves, and four sharp curves (see Fig.…”
Section: Aggressive Autonomous Drivingmentioning
confidence: 99%
“…We collected a human-controlled driving dataset, with a data rate of 10 Hz, to train our network by expanding the methods used in our previous work [23]. We found that the dataset should comprise three types of distinct maneuvers in order for the neural network to accurately represent the vehicle dynamics for various friction conditions: i) Zig-zag driving at low speeds (20 − 25 km/h) on the race track, in both clockwise and counter-clockwise directions.…”
Section: Aggressive Autonomous Drivingmentioning
confidence: 99%